DNA Sequencing From Experimental Methods to Bioinformatics - Alphey, Luke (Introduction to Biotechniques Series., 1997)
This guide to the techniques and protocols for DNA sequencing includes chapters on bioinformatics and electronic and Internet databases. By explaining the options available and their merits, it allows newcomers to the field to decide which method is the most suitable for their application.